(untitled) (Iranian Journal of Kidney Diseases, 2016)
Grape seed procyanidin B2 (GSPB2) exerts a variety of potent protective pharmacological effects on diabetic complications. The renal protective effects of GSPB2 and the target protein mimecan regulated by GSPB2, discovered in a previous quantitative proteomic analysis, were assessed in mice with diabetic nephropathy Twenty-four db/db mice were divided into 2 groups of the vehicle-treated and GSPB2-treated (30 mg/kg/d) diabetic groups. All animals were observed for 10 weeks. Treatment with GSPB2 resulted in an improvement in body weight increase and serum levels of triglyceride, total cholesterol, advanced glycation end products, and urinary albumin excretion in comparison with the vehicle-treated diabetic mice (P < .05), although these levels were still higher than those in the control group. Treatment with GSPB2 significantly reduced the extent of glomerular basement membranes thickening, mesangial expansion, and glomerular area as well. Mimecan protein expressions in diabetes mellitus were decreased approximately by 28% when compared with those in the control group (P < .05), and restored remarkably after GSPB2 treatment (P < .05). The expression of nuclear factor-κB (NF-κB) p65 in nuclear extracts, markedly higher in the diabetic mice than in the controls, was significantly suppressed by GSPB2. The findings of this study revealed that mimecan might become a new therapeutic target in the future and indicated that GSPB2 had beneficial effects not only on oxidative stress, but also on renal fibrosis, particularly in the diabetic kidney.